Reconnecting the Dots for the Payment Service Directive 2 - Compatible Asian Financial Network - Gongpil Choi; Meeyoung Park (East Asian Economic Review (EAER), 2019)
Unlike the popular belief, digital transformation mainly gets stymied by legal and regulatory issues related with legacy institutions in Asia rather than technical difficulties. The real challenges triggered by the PSD2 (Payment Services Directive 2) are how the region would overcome the overly fragmented, centralized, and hierarchical legacy framework to allow necessary changes to respond to the digital single market initiatives as promulgated by the European counterpart. The PSD2 is expected to bring about substantial changes in the payment ecosystem by allowing payment service providers to access customers' accounts and transactions information via API that have been traditionally controlled by banks. This paper suggests an incentive-compatible mechanism design for open collaboration among legacy institutions in the region to help them adapt to the PSD2. As evidenced by case studies in Korea, the Asian equivalent of PSD2 can be implemented and further expanded to create region-wide PCS (payment-clearing-settlement) network by reconnecting the dots of legacy infrastructures. These decentralized, diverse, small payment networks can be further combined with the expanded RTGS-CDS platform to evolve into the next phase of Asian Financial Network.
Keywords: D85; F02; F42; F68; O19; O33; O57; P31; P51; 330; PSD2; Digital Transformation; Financial Network; Governance; Mechanism Design; Asia